2022
DOI: 10.3390/healthcare10081544
|View full text |Cite
|
Sign up to set email alerts
|

Delirium in Nursing Home Residents: A Narrative Review

Abstract: Delirium is an important component of the geriatric syndromes and has been recognized to negatively influence the prognosis of older people in hospital and in a post-acute setting. About 2–5% of older people world-wide live in nursing homes and are characterized by functional impairment, cognitive decline, dementia, comorbidities, and polypharmacotherapy, all factors which influence the development of delirium. However, in this setting, delirium remains often understudied. Therefore, in this narrative review, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 81 publications
0
16
0
Order By: Relevance
“…As highlighted previously, adversities such as dysphagia and delirium are complications of multimorbidity and resulting frailty, 3 , 4 and are both independently associated with mortality. 8 , 54 As such, both of these conditions may be rightly viewed as late signals of end-of-life decline in LTC residents because they are indicators of severe cognitive and physical dysregulation or impairment in an already frail and vulnerable population. However, this interpretation is limited in the current study because of a lack of context.…”
Section: Discussionmentioning
confidence: 99%
“…As highlighted previously, adversities such as dysphagia and delirium are complications of multimorbidity and resulting frailty, 3 , 4 and are both independently associated with mortality. 8 , 54 As such, both of these conditions may be rightly viewed as late signals of end-of-life decline in LTC residents because they are indicators of severe cognitive and physical dysregulation or impairment in an already frail and vulnerable population. However, this interpretation is limited in the current study because of a lack of context.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of the prevalence of delirium in long-term care settings vary widely (1%-70%), with heterogeneity due to methods to ascertain delirium and case-mix of residents (e.g., age, % with dementia). 33,34 Among nursing home residents with acute illness, delirium onset is common (17.7% within 14 days). 35 Delirium is stressful to families 36 and creates additional stress and strain on nurses caring for those patients.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the rate of delirium in nursing home residents on short‐acting opioids was ~20 per 100 person‐years. Estimates of the prevalence of delirium in long‐term care settings vary widely (1%–70%), with heterogeneity due to methods to ascertain delirium and case‐mix of residents (e.g., age, % with dementia) 33,34 . Among nursing home residents with acute illness, delirium onset is common (17.7% within 14 days) 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Other significant risk factors associated with delirium in these settings include dehydration, falls, use of physical restraints, and SARS-CoV-2 infection. In nursing homes, 10 delirium increases risks of re-hospitalization, mortality, and worse functional outcomes, yet delirium remains understudied in these settings.…”
Section: Introduction and Pathophysiologymentioning
confidence: 99%
“…Other significant risk factors associated with delirium in these settings include dehydration, falls, use of physical restraints, and SARS-CoV-2 infection. In nursing homes, 10 delirium increases risks of re-hospitalization, mortality, and worse functional outcomes, yet delirium remains understudied in these settings. To address delirium burden in older adults, national guidelines in the US and UK outline risk factors, clinical indicators, prevention strategies, and management recommendations.…”
Section: Introduction and Pathophysiologymentioning
confidence: 99%